The Effect of Training and Work Motivation On Employee Performance at Bank Sumsel Babel - Ryanza Arief Hidayah; Isnurhadi Isnurhadi; Muhammad Yusuf; Marlina Widiyanti (Return : Study of Management, Economic and Bussines, 2024)
This study was conducted with the aim of determining the influence of training and work motivation on employee performance at Bank Sumsel Babel. The population in this study is all employees at Bank Sumsel Babel in 2023 as many as 3,312 employees. Based on calculations using the Slovin formula, the sample that became respondents in this study was as many as 120 employees of Bank Sumsel Babel. The results of multiple linear regression analysis show that training and work motivation have a positive and significant effect on employee performance. Training, it is hoped that the Bank of South Sumatra Babel in providing training can adjust to what employees need in supporting their work. Work motivation, it is hoped that the boss can motivate his work team to be able to build good relationships and support each other in order to provide work results that are in accordance with the company's expectations.